AGE DETERMINATION FROM EPIPHYSEAL UNION AT KNEE JOINT (Journal of Forensic Medicine & Toxicology, 2012)
Medico-legal importance of age-estimation in various civil and criminal cases is well documented. Physical, dental and radiological changes are useful parameters for estimation of age. After the age of 16 years, epiphyseal union on radiological examination is of vital importance.1 During January to March 2011, 204 persons of known age (200 subjects and 4 control samples), original native of Ahmedabad region were selected for the study from the patients and their relatives at KesarSAL Hospital, Ahmedabad. The subjects were equally distributed as of either sex and in the 5 age-groups of one year each between the 13-18 years. After taking written informed consent, x ray of both the knees was taken in AP view. It was found that the epiphyseal fusion at lower end of femur and upper end of tibia is bilaterally symmetrical. It processes and progresses simultaneously together. It males it started at the age of 15-16 years and is completed by the age of 16.5-17.5 years. In comparison, females were ahead of males by 1-1.5 years.
Keywords: Epiphyseal union; Knee joint; Age determination